2017
DOI: 10.3390/en10070848
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a Solar-Driven Trigeneration System with Nanofluid-Based Parabolic Trough Collectors

Abstract: Abstract:The objective of this work was to optimize and to evaluate a solar-driven trigeneration system which operates with nanofluid-based parabolic trough collectors. The trigeneration system includes an organic Rankine cycle (ORC) and an absorption heat pump operating with LiBr-H 2 O which is powered by the rejected heat of the ORC. Toluene, n-octane, Octamethyltrisiloxane (MDM) and cyclohexane are the examined working fluids in the ORC. The use of CuO and Al 2 O 3 nanoparticles in the Syltherm 800 (base fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…Finally, the exergy efficiency and entropy generation rate were investigated by some researchers [58][59][60][61]. On the later issue, it was concluded that application of nanofluid enhances the exergy efficiency [62] and lead to a decrease in entropy generation rate [59].…”
Section: Numerical Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the exergy efficiency and entropy generation rate were investigated by some researchers [58][59][60][61]. On the later issue, it was concluded that application of nanofluid enhances the exergy efficiency [62] and lead to a decrease in entropy generation rate [59].…”
Section: Numerical Studiesmentioning
confidence: 99%
“…Bellos et al [62,79] numerically modeled the effect of Al 2 O 3 /syltherm 800 and CuO/syltherm 800 nanofluids to study their effect on thermal enhancement of the PTC. In reference [79] up to 4% volume fraction of both Al 2 O 3 and CuO was examined.…”
Section: Investigationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results reported in these references showed that the maximum allowable temperature at which the absorption coefficient does not change significantly is as high as 500 • C. This makes metal-oxide nanoparticles suitable for use at very high temperatures in heat transfer fluids in CSP plants.Heat transfer fluids with nanoparticles provide significant benefits in CSP solar power plants because of the enhancement of heat transfer, thermodynamic and thermophysical properties in absorbing heat induced by solar radiation. Enhanced heat transfer by the use nanofluids yields improvement to the receiver performance and absorption efficiency that may reduce the number of CSP collectors required to produce power using the basis fluid as thermal oil [28][29][30][31][32][33][34][35].It has been shown theoretically and experimentally that, in low-temperature solar collectors at around 100 • C, efficiency can be improved by using nanofluids [10,11]. A paper was presented by Calise and Vanoli [12] on the design procedure and a simulation model of a novel concentrating PVT collector.…”
mentioning
confidence: 99%
“…Concentrating solar collectors are technologies that can be applied in a great range of applications, such as space-heating, space-cooling, refrigeration, domestic hot water production, chemical processes, industrial heat, desalination, and electricity production [3][4][5].…”
Section: Introductionmentioning
confidence: 99%